1996
DOI: 10.1002/art.1780390507
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐endothelial cell IgG antibodies from patients with Wegener's granulomatosis bind to human endothelial cells in vitro and induce adhesion molecule expression and cytokine secretion

Abstract: Objective. To elucidate the role of antiendothelial cell antibodies (AECA) in vascular inflammation in patients with Wegener's granulomatosis (WG). Methods. IgG fractions from 3 AECA‐positive WG patients, IgG from 3 AECA‐negative WG patients, and IgG from healthy donors were tested for their ability to: a) bind to endothelial cells and to display complement‐dependent or antibody‐dependent cellular cytotoxicity, b) modulate cell membrane expression of adhesion molecules, as evaluated by cytofluorometry and by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 127 publications
(40 citation statements)
references
References 30 publications
0
40
0
Order By: Relevance
“…We report the first evidence that AECAs are capable, not only of inducing expression of adhesion molecule (10) and sustaining leukocyte adhesion to vascular EC (11), but also of initiating apoptosis of the cells and thereby exposing anionic PL. The exposure of PS on EC by AECA may be important in triggering the production of antiphospholipid Ab (aPL) in connective tissue diseases.…”
Section: Introductionmentioning
confidence: 84%
“…We report the first evidence that AECAs are capable, not only of inducing expression of adhesion molecule (10) and sustaining leukocyte adhesion to vascular EC (11), but also of initiating apoptosis of the cells and thereby exposing anionic PL. The exposure of PS on EC by AECA may be important in triggering the production of antiphospholipid Ab (aPL) in connective tissue diseases.…”
Section: Introductionmentioning
confidence: 84%
“…Indeed, AECA-positive polyclonal IgG fractions from WG and SLE sera induce an endothelial perturbation in vitro, which is characterized by: (i) increased ADM expression, (ii) leukocyte adherence and (iii) enhanced secretion of proinflammatory cytokines and chemokines [35][36][37][38]. All of these effects might potentially cooperate in inducing the vessel wall inflammatory processes characteristic of vasculitis in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…It seems that a large, highly heterogeneous group of antigens can be recognized by anti-EC antibodies. Some anti-endothelial antibodies, such as those detected in Kawasaki disease, recognize cytokine-inducible molecules, while others, such as those detected in Wagener's granulomatosis and microscopic polyangitis, recognize constitutive EC antigens (Del Papa et al, 1996). Studies in vitro have shown that some anti-EC antibodies may trigger complement activation or anti-body-dependent cellular cytotoxicity.…”
Section: Anti Endothelial Cell Antibodiesmentioning
confidence: 99%
“…The studies in vitro show that complement activation products induce adhesion molecule expression by cultured ECs. C1q induces E-selectin, ICAM-1 and VCAM-1 (Del Papa et al, 1996) and C5a can upregulate P-selectin expression (Foreman et al, 1994). Immune complex and complement-mediated vessel damage in vivo require adhesion molecule expression and function.…”
Section: The Endothelial Cell As An Inflammation Amplifiermentioning
confidence: 99%